Contamination of herbal medicinal products in low-and-middle-income countries: A systematic review - Kwabena F.M. Opuni; James-Paul Kretchy; Kofi Agyabeng; Joseph A. Boadu; Theodosia Adanu; Samuel Ankamah; Alexander Appiah; Geralda B. Amoah; Mariam Baidoo; Irene A. Kretchy (Heliyon, 2023)
The use of herbal medicinal products (HMPs) has grown significantly across low-and-middle-income countries (LMICs). Consequently, the safety of these products due to contamination is a significant public health concern. This systematic review aimed to determine the prevalence, types, and levels of contaminants in HMPs from LMICs. A search was performed in seven online databases, i.e., Africa journal online (AJOL), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Directory of Open Access Journals (DOAJ), Health Inter-Network Access to Research Initiative (HINARI), World Health Organization Global Index Medicus (WHO GIM), Scopus, and PubMed using appropriate search queries and reported as per the “Preferred Reporting Items for Systematic Reviews and Meta-Analyses” (PRISMA) guidelines. Ninety-one peer-reviewed articles published from 1982 to 2021 from 28 different countries across four continents were included in the study. Although metals, microbial, mycotoxins, pesticides, and residual solvents were the reported contaminants in the 91 articles, metals (56.0%, 51/91), microbial (27.5%, 25/91), and mycotoxins (18.7%, 17/91) were the most predominant. About 16.4% (1236/7518) of the samples had their contaminant levels above the regulatory limits. Samples tested for microbial contaminants had the highest proportion (46.4%, 482/1039) of contaminants exceeding the regulatory limit, followed by mycotoxins (25.8%, 109/423) and metals (14.3%, 591/4128). The proportion of samples that had their average non-essential metal contaminant levels above the regulatory limit was (57.6%, 377/655), 18.3% (88/480), 10.7% (24/225), and 11.3% (29/257) for Pb, Cd, Hg, and As, respectively. The commonest bacteria species found were Escherichia coli (52.3%, 10/19) and Salmonella species (42.1%, 8/19). This review reported that almost 90% of Candida albicans and more than 80% of moulds exceeded the required regulatory limits. HMP consumption poses profound health implications to consumers and patients. Therefore, designing and/or implementing policies that effectively regulate HMPs to minimize the health hazards related to their consumption while improving the quality of life of persons living in LMICs are urgently needed.